Understanding the behavior of new plasmonic probes with sub-nanometric resolution in field enhanced scanning optical microscopy - Perassi, Eduardo Marcelo (2011)
Recently, using field enhanced scanning optical microscopy (FESOM), a new kind of plasmonic nanostructured probes has been introduced capable to achieve subnanometric vertical resolution on atomically flat samples. These plasmonic probes consisting in silica (SiO2) microspheres decorated with 5 nm diameter spherical Ag nanoparticles (NPs) exhibit a multiple peaked experimental extinction spectra in colloidal dispersion. The subnanometric resolution achieved in FESOM is observed when they are attached to a metal tip and illuminated at 632 nm. On the contrary, these probes lack of resolution in FESOM measurements upon 532 nm laser light illumination. In this work, the complex extinction properties of these probes as well as their near field optical properties are compared and analyzed by means of rigorous electrodynamic simulations. The calculations show that the far and near field optical behavior can only be explained in a consistent way in terms of the plasmonic response of small Ag NPs clusters on the silica surface. Using these cluster configurations, the near field simulations of the optical response are also found to be in excellent agreement with the experimental FESOM approach curves, demonstrating in this way the subnanometric resolution achieved at 632 nm and the almost null response at 532 nm. © 2011 American Chemical Society.